(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The present study objective was to treat through the cognitive behavioral therapy, the patient anxiety disorder who are currently in medical treatment, whose diagnosis is idiopathic purpura. Therefore, three patients were part of the study, all of them female, aged 27-70 years. The applied method in this study was based on 10 psychotherapy sessions, and the use of a scale to measure the intensity of the symptoms of anxiety, the Beck Anxiety Inventory (BAI), along with the blood sample exams. After the psychotherapy follow-through, regardless the use of the medication to control the decrease of platelets, it was observed a lower level of anxiety and increased platelets in those three patients. According to the results of this study it may be suggested it’s continuity, with a larger number of patients of different ages and gender.